ATTITUDE TOWARDS INFLUENZA VACCINE AMONG THE GENERAL POPULATION OF LATVIA DURING THE COVID-19 PANDEMIC - Dzirne, Denija; Boginska, Zanda; Strods, Gunars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Annual influenza epidemics are associated with substantial morbidity and mortality, especially in elderly and in those with underlying diseases. During the global COVID-19 pandemic WHO and CDC have emphasized the importance of reducing risk of influenza virus spread and protecting high risk patient groups from complications caused by the influenza virus. Influenza vaccine may also reduce the burden on healthcare systems while we wait for a COVID-19 vaccine. Although the influenza vaccine has been around for a while, there are still many who question the efficiency, safety and usefulness of it. The article aims to study the attitude of the Latvian adult population towards influenza vaccine during the COVID-19 pandemic. Materials and methods: a quantitative, cross-sectional study based on an anonymous online survey consisting of 12 questions. Data was analysed by using descriptive statistics and Pearson correlation. Results: major part of the respondents do not support influenza vaccine, but almost a half support the vaccination or have changed their attitude towards it during the COVID-19 pandemic. Data shows lack of knowledge about influenza infection, influenza vaccine and vaccine side effects, therefore further educational campaigns should be developed for the general population.